If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2990 = 4 * 660 + 6y Multiply 4 * 660 2990 = 2640 + 6y Solving 2990 = 2640 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 2990 + -6y = 2640 + 6y + -6y Combine like terms: 6y + -6y = 0 2990 + -6y = 2640 + 0 2990 + -6y = 2640 Add '-2990' to each side of the equation. 2990 + -2990 + -6y = 2640 + -2990 Combine like terms: 2990 + -2990 = 0 0 + -6y = 2640 + -2990 -6y = 2640 + -2990 Combine like terms: 2640 + -2990 = -350 -6y = -350 Divide each side by '-6'. y = 58.33333333 Simplifying y = 58.33333333
| 12x+9y=310 | | -2(z-9)=-24 | | y-10=-2(x+2) | | 7u-6u+2=20 | | 2990=4*650+6y | | .5x-9=.2x | | Y-2=-1(x+7) | | 4(cos^2(2x))-2=0 | | -25d-50= | | 2990=4*640+6y | | x+y-8x+6y-125=0 | | X-15=-50 | | 70=(4y-30) | | 3x-10y=-22 | | (1-x)+3x=-2(x+1) | | 5x-20+2x+53=180 | | -4z-1=12 | | x+5/x+4=7 | | (-8b)-(-12b)+2=(-10) | | 5x-20+2x-53=180 | | 7b-14= | | 14m-3=12m-15 | | 7t-5t-1=3 | | 2(w+2)=10 | | Y-3=8(x-2) | | 2990=4x+6y | | 3x(8+2)= | | 5p-(-20)-(-11)=(-14) | | 3y+12=27-2y | | 8x^2+36x-288=0 | | (-17j)-2j=(-19) | | 7x^2+2x=3600 |